2012
DOI: 10.1111/j.1439-0531.2012.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Markers of the Carbonic Anhydrase II Gene Associated with Egg Production and Reproduction Traits in Tsaiya Ducks

Abstract: In our previous cDNA microarray study, we found that the carbonic anhydrase II (CA2) gene is one of the differentially expressed transcripts in the duck isthmus epithelium during egg formation period. The aim of this study was to identify the single-nucleotide polymorphisms (SNPs) in the CA2 gene of Tsaiya ducks. The relationship of SNP genotype with egg production and reproduction traits was also investigated. A total of 317 ducks from two lines, a control line with no selection and a selected line, were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Microarray technologies enable the examination of expression levels of thousands of genes in a single hybridization experiment. Microarray analyses can permit the understanding of biological pathways important in various physiological processes [4] and may therefore contribute to improvements in important economic parameters in poultry, like egg production and reproduction traits in ducks or feed efficiency and growth in broilers [8] [10] . Furthermore, behavioural disorders, like feather pecking, a serious animal welfare and economically important problem, especially in the laying hen husbandry has been examined by using microarray analyses in several studies [11] [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Microarray technologies enable the examination of expression levels of thousands of genes in a single hybridization experiment. Microarray analyses can permit the understanding of biological pathways important in various physiological processes [4] and may therefore contribute to improvements in important economic parameters in poultry, like egg production and reproduction traits in ducks or feed efficiency and growth in broilers [8] [10] . Furthermore, behavioural disorders, like feather pecking, a serious animal welfare and economically important problem, especially in the laying hen husbandry has been examined by using microarray analyses in several studies [11] [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Studying hormonal profiles during egg-laying cycles and gene expression patterns during follicular development will provide insights into the endocrine regulatory mechanisms of follicular maturation and ovulation and reveal the key roles of genes that determine oviposition cycle and egg-laying rate. Discovery of these genes is also important for molecule-aided selection of egg-laying performance [9]. The endocrine mechanisms that regulate the egg-laying cycle has been documented for the chickens [6,10,11], in which egg laying and ovarian follice recruitment are almost continuous, and so have the secretion patterns of progesterone and pgFM for graylag goose ( Anser anser ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dunn et al reported that CA2 gene polymorphism is associated with chicken egg shape ( Dunn et al, 2009 ). Especially, Chang et al found that CA2 is one of the differentially expressed transcripts in the duck isthmus epithelium during the egg formation period, and they confirmed that some SNPs in the 3′-UTR of the CA2 gene in Tsaiya ducks are associated with egg reproduction traits ( Chang et al, 2013 ). We found 13 genes located in CHROMOSOME 29 that affect EP66w, including DAZAP1, GAMT, NDUFS7, CIRBP, FAM174C, MIDN, STK11, SBNO2, POLR2E, ARHGAP45, GRIN3B, TMEM259, and WDR18.…”
Section: Discussionmentioning
confidence: 94%